Christmas in Peachtree Bluff : a novel - Harvey, Kristy Woodson (Harvey, Kristy Woodson. Peachtree Bluff novel., 2021)
"In the newest installment of USA TODAY bestselling author Kristy Woodson Harvey's Peachtree Bluff series, three generations of the Murphy women must come together when a hurricane threatens to destroy their hometown-and the holiday season in the process"--